FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS KOTABARU KABUPATEN KOTABARU - Hotimah, Husnul; Kabuhung, Elvine Ivana; Oktaviannor, Husda (Jurnal Ilmiah Maternal, 2023)
Pneumonia is an acute respiratory infection that attacks the lower parts of the lungs, namely the alveoli. The factors that can influence the occurrence of pneumonia in toddlers include the age of the toddler, incomplete immunization status and status of exclusive breastfeeding. Data from the Kotabaru Health Center recorded that the number of children under five with pneumonia in 2021 was 118 cases of pneumonia (17.4%) out of 678 children under five. The Objective is to find out the factors associated with the incidence of pneumonia in toddlers. The method used analytic survey research method with a cross sectional approach. The sample used a purposive sampling technique of 54 sick toddlers who had pneumonia aged 12-60 months. Data collection came from secondary data. The result is there is a relationship between basic immunization status and the incidence of toddlers sick with pneumonia in (p.value = 0.000 <0.05). There is a relationship between the status of exclusive breastfeeding and the incidence of children under five suffering from pneumonia (p.value = 0.000 <0.05). Conclusion, Toddler age, incomplete immunization status and exclusive breastfeeding status are related to the incidence of pneumonia.